Permasalahan Perdagangan Manusia dalam Perspektif Hukum Internasional - Alex Tribuana Sutanto (Terekam Jejak Publisher, 2024)
Inadequate legal regulations in a country cause difficulty in arresting human traffickers, both at the national and international levels. In fact, it is difficult to bring traffickers to justice1. Apart from that, many victims do not obtain the rights that are regulated in legal regulations. This situation highlights the importance of improving and more effective law enforcement to protect victims and punish traffickers. This research was conducted to elaborate on Human Trafficking regulations in international law and describe the obstacles faced in handling human trafficking victims in Indonesia. The research was carried out using literature or empirical normative research methods and juridical research methods, namely elaborating each material followed by observing policy and regulatory studies. The results of the research are that national law has strictly regulated the criminal act of human trafficking in Law of the Republic of Indonesia Number 21 of 2007 concerning the Eradication of the Criminal Act of Human Trafficking. This law was formed as a form of the Palermo Protocol which was ratified in Indonesia. Legal protection for victims of criminal acts of human trafficking is also guaranteed in the law by imprisoning the perpetrators of these crimes and providing legal rights for victims.